Find the coefficient of the series

Let k = 0 n 1 k ! ( n 1 ) ! = 1 + 1 n 1 + 1 ( n 1 ) ( n 2 ) + + 1 ( n 1 ) ! = k = 0 a k n k . \sum_{k=0}^{n-1} \frac{k!}{(n-1)!} = 1 + \frac{1}{n-1} + \frac{1}{(n-1)(n-2)} + \cdots + \frac{1}{(n-1)!} = \sum_{k=0}^\infty \frac{a_k}{n^k}.

What is the value of a 6 a_6 ?


The answer is 203.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

Star Chou
Jul 12, 2018

a 0 + a 1 n + a 2 n 2 + = 1 + 1 n 1 ( 1 + 1 n 2 + 1 ( n 2 ) ( n 3 ) + + 1 ( n 2 ) ! ) = 1 + 1 n 1 ( a 0 + a 1 n 1 + a 2 ( n 1 ) 2 + ) = 1 + ( 1 n + 1 n 2 + 1 n 3 + ) ( a 0 + a 1 ( 1 n + 1 n 2 + 1 n 3 + ) + a 2 ( 1 n + 1 n 2 + 1 n 3 + ) 2 + ) = 1 + a 0 n + a 0 + a 1 n 2 + a 0 + 2 a 1 + a 2 n 3 + \begin{aligned} a_0 + \frac{a_1}{n} + \frac{a_2}{n^2} + \cdots &= 1 + \frac{1}{n-1} \left (1 + \frac{1}{n-2} + \frac{1}{(n-2)(n-3)} + \cdots + \frac{1}{(n-2)!} \right ) \\ &= 1 + \frac{1}{n-1} \left (a_0 + \frac{a_1}{n-1} + \frac{a_2}{(n-1)^2} + \cdots \right ) \\ &= 1 + \left (\frac{1}{n} + \frac{1}{n^2} + \frac{1}{n^3} + \cdots \right ) \left (a_0 + a_1 \left (\frac{1}{n} + \frac{1}{n^2} + \frac{1}{n^3} + \cdots \right ) + a_2 \left (\frac{1}{n} + \frac{1}{n^2} + \frac{1}{n^3} + \cdots \right )^2 + \cdots \right ) \\ &= 1 + \frac{a_0}{n} + \frac{a_0+a_1}{n^2} + \frac{a_0+2a_1+a_2}{n^3} + \cdots \end{aligned} Hence we obtain a 0 = 1 a_0 = 1 and the recurrence a m + 1 = k = 0 m ( m k ) a k a_{m+1} = \displaystyle \sum_{k=0}^m {{m}\choose{k}} a_k , which matches the recurrence for the Bell numbers B m B_m .

So a 6 = a 0 + 5 a 1 + 10 a 2 + 10 a 3 + 5 a 4 + a 5 = a 0 + 5 a 1 + 10 a 2 + 10 a 3 + 5 a 4 + ( a 0 + 4 a 1 + 6 a 2 + 4 a 3 + a 4 ) = 2 a 0 + 9 a 1 + 16 a 2 + 14 a 3 + 6 ( a 0 + 3 a 1 + 3 a 2 + a 3 ) = 8 a 0 + 27 a 1 + 34 a 2 + 20 ( a 0 + 2 a 1 + a 2 ) = 28 a 0 + 67 a 1 + 54 ( a 0 + a 1 ) = 82 a 0 + 121 a 1 = 203 \begin{aligned} a_6 &= a_0 + 5 a_1 + 10 a_2 + 10 a_3 + 5 a_4 + a_5 \\ &= a_0 + 5 a_1 + 10 a_2 + 10 a_3 + 5 a_4 + (a_0 + 4 a_1 + 6 a_2 + 4 a_3 + a_4) \\ &= 2 a_0 + 9 a_1 + 16 a_2 + 14 a_3 + 6 (a_0 + 3 a_1 + 3 a_2 + a_3) \\ &= 8 a_0 + 27 a_1 + 34 a_2 + 20 (a_0 + 2 a_1 + a_2) \\ &= 28 a_0 + 67 a_1 + 54 (a_0 + a_1) \\ &= 82 a_0 + 121 a_1 \\ &= 203 \end{aligned}

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...